Gwadar Deep Sea Port’s Emergence as Regional Trade and Transportation Hub: Prospects and Problems - Zahid Anwar (Journal of Political Studies, 2010)
The deep-sea port at Gwadar is visualized as becoming a regional hub, serving commercial traffic to and from Central Asian states and Afghanistan, the Middle East, the Persian Gulf, Xinjiang, Iran, and South East Asia. The development of the Gwadar port holds out for the regional countries immense economic returns. A road from Gwadar to Saindak, said to be the shortest route between Central Asia and the sea, is under construction. Goods and oil and gas reserves from these countries could be shipped to global markets. It will nearly halve the overland distance from China’s landlocked western provinces to the sea: from about 4,000 km to China’s east coast, to just 2,000 km south to Gwadar. The Gwadar port and the highways connecting it to Afghanistan reduce the distances of Pakistan-Central Asia traffic by about 500 km. The construction of the Gwadar port is an important component of Pakistan’s overall initiative to facilitate trade with the landlocked states of Central Asia.